2013
DOI: 10.1155/2013/192582
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mechanisms of Idiopathic Epiretinal Membrane Formation

Abstract: The pathogenesis of idiopathic epiretinal membranes (iERMs), a common pathology found in retina clinics, still eludes researchers to date. Ultrastructural studies of iERMs in the past have failed to identify the cells of origin due to the striking morphologic changes of cells involved via transdifferentiation. Thus, immunohistochemical techniques that stain for the cytostructural components of cells have confirmed the importance of glial cells and hyalocytes in iERM formation. The cellular constituents of iERM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 34 publications
4
86
0
6
Order By: Relevance
“…To assess the cellular localization of the identified proteins (Figure 2b, Supporting Information Table S3), we used Phobius software (Käll, Krogh, & Sonnhammer, 2004), and more than 99% of intravitreal proteins were identified either as being extracellular or as having a transmembrane domain. This corresponds well with the fact that most vitreous proteins are expected to be secreted or shed from the surrounding tissues (Joshi et al, 2013; Loukovaara et al, 2015). …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…To assess the cellular localization of the identified proteins (Figure 2b, Supporting Information Table S3), we used Phobius software (Käll, Krogh, & Sonnhammer, 2004), and more than 99% of intravitreal proteins were identified either as being extracellular or as having a transmembrane domain. This corresponds well with the fact that most vitreous proteins are expected to be secreted or shed from the surrounding tissues (Joshi et al, 2013; Loukovaara et al, 2015). …”
Section: Resultssupporting
confidence: 76%
“…An older age and the development of anomalous posterior vitreous detachment (PVD) are the generally accepted nonmodifiable key risk factors in the iERM pathogenesis (Cheung et al, 2017). In addition, a number of inflammatory and immunomodulatory processes, chronic oxidative insult, proteolysis, and cytoskeleton remodeling, have been implicated in its formation (Joshi, Agrawal, & Christoforidis, 2013; Pollreisz et al, 2013). Metabolically, the retina is the most oxygen‐consuming tissue in the human body (Arden, Sidman, Arap, & Schlingemann, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…From a histopathologic point of view, the fibrotic process that is associated with the growth of ERMs involves diverse cell types, including hyalocytes, fibroblasts, and glia cells, 24 which are activated by different fibroblast-signaling pathways and which participate in the secretion of extracellular-matrix components. 25 Activated Müller glia cells contribute to the formation of ERMs.…”
Section: Discussionmentioning
confidence: 99%
“…24,30 Transforming growth factor-b-1 and the nerve growth factor were shown to play a crucial role in fibroblast activities and were detected in the vitreal humor of each of the eight patients with idiopathic ERMs. 30 Kohno et al 25 demonstrated that TGF-b-2 stimulates the differentiation of hyalocytes into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of fibrocellular tissue on the inner limiting membrane (ILM) due to a break in it following posterior vitreous detachment (PVD) is the pathogenesis of idiopathic ERMs. 1 A secondary ERM has different properties from an idiopathic ERM, because several inflammatory and vascular processes take role in its pathogenesis. 2,3 Retinal vascular diseases, diabetes mellitus (DM), uveitis, ocular traumas, argon laser photocoagulation, retinal tears, and detachments are the most known etiologic factors of secondary ERMs.…”
Section: Introductionmentioning
confidence: 99%